Bio-based high performance thermosets: Stabilization and reinforcement of eugenol-based benzoxazine networks with BMI and CNT. (June 2015) - Dumas, Ludovic; Bonnaud, Leïla; Olivier, Marjorie; Poorteman, Marc; Dubois, Philippe
Graphical abstract: Highlights: Robust synthesis of a bio based bis-benzoxazine. Copolymerization with a bismaleimide. Adjustment of crosslinking density with the comonomère content. Excellent interaction of carbon nanotubes with benzoxazine precursor. Nanohybrid formation with excellent thermomechanical properties. Abstract: This work presents the solventless synthesis, the reinforcement and the thermal stabilization of bio-based bis-benzoxazine resins derived from eugenol. The structure of this benzoxazine monomer was confirmed by 1 H NMR. The polymerization and degradation of the precursor have been investigated and monitored by DSC and TGA and showed a limited crosslinking ability due to the steric hindrance of the eugenol based aromatic ring. A bis-maleimide (bMI) has been used to stabilize the benzoxazine moiety while it undergoes also a copolymerization through an ene -addition. Depending on its relative content, the bis-maleimide proved to limit the thermal degradation of the bis-benzoxazine monomer and allowed the formation of a dense crosslinked network with high thermomechanical stability. Furthermore, the properties of the network were significantly improved by the incorporation of a small amount of carbon nanotubes (CNTs) with an increase of the Tg as high as 60 °C. The combination of bMI and CNTs will allow the use of this new bio-based benzoxazine resin as matrices for the preparation of sustainable high performance biocomposite materials.